TNF-α blockade suppresses pericystic inflammation following anthelmintic treatment in porcine neurocysticercosis. - Siddhartha Mahanty; Miguel A Orrego; Carla Cangalaya; M Paz Adrianzen; Gianfranco Arroyo; Juan Calcina; Armando E Gonzalez; Héctor H García; Cristina Guerra-Giraldez; Theodore E Nash; Cysticercosis Working Group in Peru (Public Library of Science (PLoS), 2017)
Neurocysticercosis (NCC) is an infection of the brain with the larval cyst of the tapeworm, Taenia solium. Cysticidal treatment induces parasite killing resulting in a post inflammatory response and seizures, which generally requires corticosteroid treatment to control inflammation. The nature of this response and how to best control it is unclear. We investigated the anti-inflammatory effects of pretreatment with etanercept (ETN), an anti-tumor necrosis factor agent, or dexamethasone (DEX), a high potency corticosteroid, on the post treatment inflammatory response in naturally infected pigs with neurocysticercosis after a single dose of the cysticidal drug praziquantel (PZQ).We followed the methods from a previously developed treatment model of NCC in naturally infected swine. The four study groups of infected pigs included 3 groups treated with PZQ on day 0: PZQ-treated alone (100 mg/kg PO; n = 9), pretreated with dexamethasone (DEX, 0.2 mg/kg IM administered on days -1, +1 and +3; n = 6), and pretreated with etanercept (ETN, 25 mg IM per animal on days -7 and 0; n = 6). The fourth group remained untreated (n = 3). As measured by quantitative RT-PCR, ETN pretreatment depressed transcription of a wide range of proinflammatory, regulatory and matrix protease encoding genes at 120 hr post PZQ treatment in capsules of cysts that demonstrated extravasated Evans Blue (EB) (a measure of blood brain barrier dysfunction) compared to animals not receiving ETN. Transcription was significantly depressed for the proinflammatory genes tumor necrosis factor (TNF)-α, and interferon (IFN)-γ; the inflammation regulating genes cytotoxic T-lymphocyte-associated protein (CTLA)4, interleukin (IL)-13 and transforming growth factor (TGF)-β; the tissue remodeling genes matrix metalloprotease (MMP)1 and 9, tissue inhibitors of metalloproteases (TIMP)1 and 2, and the genes regulating endothelial function vascular endothelial growth factor (VEGF)1, angiopoietin (Ang)1, Ang 2, and platelet endothelial cell adhesion molecule (PECAM)-1. In contrast, transcription was only modestly decreased in the DEX pretreated pigs compared to PZQ alone, and only for TNF-α, IL-6, IFN-γ, TGF-β and Ang1. IL-10 was not affected by either ETN or DEX pretreatments. The degree of inflammation, assessed by semi-quantitative inflammatory scores, was modestly decreased in both ETN and DEX pretreated animals compared to PZQ treated pigs whereas cyst damage scores were moderately decreased only in cysts from DEX pretreated pigs. However, the proportion of cysts with EB extravasation was not significantly changed in ETN and DEX pretreated groups.Overall, TNF-α blockade using ETN treatment modulated expression of a large variety of genes that play a role in induction and control of inflammation and structural changes. In contrast the number of inflammatory cells was only moderately decreased suggesting weaker effects on cell migration into the inflammatory capsules surrounding cysts than on release of modulatory molecules. Taken together, these data suggest that TNF-α blockade may provide a viable strategy to manage post-treatment pericystic inflammation that follows antiparasitic therapy for neurocysticercosis.